METHODS OF GENERATING TEST DATA IN JSON FORMAT: MODEL-FREE APPROACH - Горщар, К.Ю. (SWorldJournal, 2026)
The article is devoted to the study of methods for generating test data in the JSON structure for performing automated API tests in a model-free manner. A common data sampling method SampleSelector is proposed, which allows for efficient sampling without